2019
DOI: 10.1017/s2045796018000847
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to maternal depressive symptoms in childhood and adolescent suicide-related thoughts and attempts: mediation by child psychiatric symptoms

Abstract: Aims The nature of the association between child psychiatric symptoms and adolescent suicide-related thoughts (SRT) and attempts (SA) remains unclear. Our objective was to assess whether child psychiatric symptoms from 6 to 10 years of age mediate the association between exposure to maternal depressive symptoms in childhood and offspring SRT and SA in adolescence. Methods A population-based cohort study was constructed by linking all eight cycles from the National Longitudinal Survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…Children of women with schizophrenia are at higher risk of developing mental disorders themselves, a key risk for self‐injury 45 . Suicidal thoughts in children of mothers with other types of mental illness are at least partly mediated by the child's psychiatric symptoms 46,47 . In our study, the differentially elevated risk of self‐injury started to become apparent in school‐age children and adolescents, when mental disorders begin to emerge, supporting this hypothesis.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Children of women with schizophrenia are at higher risk of developing mental disorders themselves, a key risk for self‐injury 45 . Suicidal thoughts in children of mothers with other types of mental illness are at least partly mediated by the child's psychiatric symptoms 46,47 . In our study, the differentially elevated risk of self‐injury started to become apparent in school‐age children and adolescents, when mental disorders begin to emerge, supporting this hypothesis.…”
Section: Discussionsupporting
confidence: 76%
“…45 Suicidal thoughts in children of mothers with other types of mental illness are at least partly mediated by the child's psychiatric symptoms. 46,47 In our study, the differentially elevated risk of self-injury started to become apparent in schoolage children and adolescents, when mental disorders begin to emerge, supporting this hypothesis. This suggests that children of women with schizophrenia should be monitored not only for emerging mental health conditions, but also thoughts of suicide or deliberate self-injury, and probably earlier than in the teen years.…”
supporting
confidence: 78%
“…Risk factors for suicide among youth include in-utero and perinatal adverse conditions, child abuse or neglect, family problems, stressful life events, social isolation, academic pressure, bullying, youth's psychiatric disorders, previous self-harm, and suicide in friends or family (Hawton, 2009; Orri et al, 2019; Rodway et al, 2016). Due to genetic and environmental reasons, exposure to parental psychopathology has been identified as a risk factor for youths’ suicide-related thoughts (suicidal ideation) and behaviors (Goodday, Bondy, Brown, Sutradhar, & Rhodes, 2020).…”
mentioning
confidence: 99%
“…Identifying environmental, child-related pathways via which exposure to maternal depression leads to suicidality (i.e., ideation and/or attempt) can inform preventive interventions targeting these putative mechanisms. Previous longitudinal studies have shown that children's mental health problems are a pathway through which exposure to maternal depression can increase the risk of youth suicidality (Goodday et al, 2020; Hammerton, Zammit, et al, 2015). However, little is known about other potential mechanisms through which the association between exposure to maternal depression and children's suicidality occurs.…”
mentioning
confidence: 99%